Pengaruh Promosi Online Terhadap Keputusan Pembelian Jasa Transportasi Online Grab di Kota Pagar Alam - Elvera; Mico, Sastra (Nusa Putra University, 2021)
This study aims to determine the effect of online promotion on purchasing decisions for online grab transportation services in Pagar Alam City. The population in this study were 75 respondents in Pagar Alam City. This research uses associative research with a quantitative approach. The sampling technique is simple random sampling, which means that members of the sample and the population are taken randomly without paying attention to the existing strata in the population. Data analysis used simple linear regression analysis and t test. The results of the simple linear regression test in this study indicate that online promotion has a positive and significant effect on the decision to purchase online grab transportation services in Pagar Alam City so that it can be seen that the simple linear regression equation is Y = 7,789 + 0.277 X. Where the constant value is 7,789 and the value The linear regression coefficient of online promotion has a positive effect. If the online promotion increases by one unit, the purchase decision will increase by 0.277 units. The results of the t test where the significant value is 0.000, which means it is smaller than 0.05, so the hypothesis is accepted..